Changes in plant diversity, plant traits and environmental variables along an urbanization gradient in Ipoh Perak - Balqis Aqila Alue (2022)
The aims of this research were (i) to examine changes in plant diversity along an urbanization gradient in Ipoh, Perak, (ii) to relate plant traits (tree height, specific leaf area (SLA), and dispersal) with the urbanization intensity, and (iii) to relate environmental conditions (ambient temperature, air humidity, and light intensity) with urbanization intensity. The urbanization intensity was determined based on the percentage of built-up area within a 1km2 area using Geographical Information Systems (GIS). A total of 12 sampling plots sized 1km2 were constructed to represent different urbanization intensities. In each plot, 40 subplots were randomly selected to form a total sampling area of 0.1 hectares, and any plants with 5cm diameter at breast height were identified at the species level. The plant height and SLA were measured while the dispersal mode was identified based on literature. The environmental data were collected during midday for three times at each plot. The findings revealed that there were 96 plant species belonging to 71 genera and 42 families in the 12 plots. Species diversity (r= -0.781; p= 0.003), richness (r= -0.842; p= 0.001), and evenness (r= -0.901; p< 0.001), declined significantly as urbanization intensity increased. The number of native species and plant height decreased with increasing urbanization intensity. Meanwhile, for SLA, the outcome demonstrated that there was no significant relationship between SLA and urbanization intensity. Endo-zoochory, hemerochory, and myrmechory were the most important dispersal modes in urban areas. The three environmental factors were also significantly associated with increasing urbanization intensity. In conclusion, environmental conditions vary with urbanization and urbanization reduces plant diversity. However, plant trait is only partially associated with urbanization. The findings from this research could help town planners in designing urban environments to achieve more sustainable development.